Supplement to the Mergelyan Theorem on the Denseness of Algebraic Polynomials in the Space C_w^0 - Bakan, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We give a supplement to the theorem on the denseness of polynomials in the space C_w^0 established by Mergelyan in 1956 for the case where algebraic polynomials are dense in C_w^0. In the case indicated, we give a complete description of all functions that can be approximated by algebraic polynomials in seminorm.